Knowledge, Attitudes, and Preparedness for Managing Pregnant and Postpartum Women with COVID-19 Among Nurse-Midwives in Kenya. (June 2022) - Maina, Rose; Kimani, Rachel Wangari; Orwa, James; Mutwiri, Bernard Daniel; Nyariki, Carolyne K.; Shaibu, Sheila; Fleming, Valerie
Introduction: Globally, maternal morbidity and mortality have increased during the COVID-19 pandemic. Given the high burden of maternal and neonatal mortality in Kenya prior to COVID-19, front line health workers, including nurse-midwives, must be competent to ensure continued quality maternal services. Knowledge and awareness of COVID-19 transmission influence nurse-midwives risk perception and ability to implement prevention strategies. Objective: We examined nurse-midwives' knowledge, attitudes, and preparedness in managing pregnant and postpartum women with COVID-19 in Kenya. Methods: A cross-sectional online survey was conducted among 118 nurse-midwives between July 2020 and November 2020. A 31-item survey comprising 15 knowledge, 11 attitude, and five preparedness questions was administered using SurveyMonkey. A link to the survey was distributed among nurse-midwives via email. Multiple logistic regression analysis was used to assess associations between the variables. A p -value <.05 was considered statistically significant. Results: Eighty-five participants were included in the final analysis (response rate 72%). Most participants were female ( n  = 69, 81.2%), 52.9% ( n  = 45) worked in labor wards, and 57.6% ( n  = 49) worked in rural hospitals. Overall, 71% ( n  = 57) of participants had sufficient knowledge about managing COVID-19 in pregnant and postpartum women. However, only 63% were willing to receive COVID-19 vaccination. Nurse-midwives working in urban areas were 3.7 times more likely to have positive attitudes than those in rural areas (odds ratio 3.724, 95% confidence interval 1.042–13.31; p  = .043). Conclusion: Nurse-midwives' responses to the Kenyan government's COVID-19 guidelines for managing and caring for pregnant women were inconsistent. Continued professional development for nurse-midwives is important to ensure they stay abreast of evolving COVID-19 guidelines for maternal health. Our findings also suggest vaccine hesitancy may be a hurdle for ongoing COVID-19 vaccination.